Alternatif Fondasi Tiang Pancang Untuk Menara Mesjid Agung Al-Mukarram - Markawie Markawie; Syariefuddin Maulana (INFO-TEKNIK, 2013)
The existence of the tower at Kuala Kapuas Kapuas Islamic Center Complex. The initial plan design of foundation. using precast reinforced concrete pile foundation with a square cross-section size of 50 cm x 50 cm with a depth of 22 meters. Another alternative is planned foundation due to change of plans superstructure. Preliminary design of foundations (piles and poerplat) subsequent to the rigors of land CPT data which is at a depth of 24 meters, calculation of the bearing capacity of the pile with a review of some of the methods in accordance with the data available land.From the analysis of the structure obtained by the forces transmitted to the stake, the maximum load bekerjauntuk one pole axial 59.6 tons and 1,527 tons for the lateral force. With concrete slab foundations diameter of 40 cm depth of 24 m configuration of 69 fruits and poer 1.3 m thick. Decrease pole group terjadi19,926 mm <smaller than would otherwise require a kind of high-rise buildings of 40 mm based on ASTM D1143-81 so that alternate designs tower foundation al-Mukarram mosque as a whole meets the technical requirements.